Evaluation of Platelet Distribution Width as an Early Predictor of Acute Kidney Injury in Extensive Burn Patients - Ming Jiang; Qingrong Zhang; Chuwei Zhang; Zihan Li; Qiqi Li; Xun Qu; Yi Zhang; Kesu Hu (Emergency Medicine International)
Background. The extensive burns devastate trauma. The research was designed to analyse the predictive value of early platelet (PLT) indices on the development of acute kidney injury (AKI) after severe burns. Methods and Results. 186 patients with extensive burns (burn area ≥30%) were eventually involved. Multivariate analyses pointed out that platelet distribution width (PDW) in the first 24 h after admission was an independent risk factor for AKI, severe AKI, and RRT requirement in patients with severe burns, and AKI risk showed an increase of 30.9% per increase of 1% in PDW (OR = 1.309, CI, 1.075–1.594, and P = 0.007). It was found that the area under the ROC curve (AUC) of PDW predicting AKI was 0.735 and that the AUC value was 0.81 for AKI after combining PDW and blood urea nitrogen (BUN). Based on the cut-off value PDW = 17.7%, patients were divided into high- (PDW ≥17.7%) and low-risk (PDW <17.7%) groups. In the KM analysis, there was a higher cumulative incidence of AKI if patients were in a high-risk group (in 30 days); and the stages of AKI showed a linear upward trend (chi-square test for linear trend P < 0.001) as there was an increase in the risk level. Conclusion. The PDW level in the early stage serves as an important risk factor for AKI, severe AKI, and RRT requirement in extensive burns. When PDW >17.7%, burn patients are not only at a higher risk for AKI but may also have higher AKI severity. Due to low cost and wide availability, PDW has the potential to be the tool that can predict AKI in extensive burn patients.